2021
DOI: 10.4142/jvs.2021.22.e69
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characteristics of bovine rotavirus A in dairy calves in China

Abstract: Background Bovine group A rotavirus (BoRVA) is a major cause of severe gastroenteritis in newborn dairy calves. Only one study has investigated the G and P genotypes among dairy calves in a few regions of China, which were G6 and P[5]. Therefore, data on the prevalence and molecular characteristics of BoRVA in dairy calves in China remains limited. Objectives The purpose of this study was to investigate the prevalence and molecular characteristics of BoRVA in dairy calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, the P[7] genotype first appearing in China was detected in Korea in 2004–2005 but has not been detected since 2014. A recent study suggests that BoRVA circulates widely among dairy calves in China, and the dominant genotype is G6P[1] [ 26 ]; however, the most prevalent genotype in Korea is G6P[5], and the P[1] genotype has not yet emerged.…”
Section: Discussionmentioning
confidence: 99%
“…However, the P[7] genotype first appearing in China was detected in Korea in 2004–2005 but has not been detected since 2014. A recent study suggests that BoRVA circulates widely among dairy calves in China, and the dominant genotype is G6P[1] [ 26 ]; however, the most prevalent genotype in Korea is G6P[5], and the P[1] genotype has not yet emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal calf diarrhea, which has the first place in calf deaths, causes significant economic losses in dairy farming around the world, due to treatment costs, labor, poor performance, growth retardation and deaths [ 1 ]. Despite scientific studies and chemotherapeutic advances on neonatal calf diarrhea, the disease still leads to high morbidity and mortality [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal calf diarrhea, which has the first place in calf deaths, causes significant economic losses in dairy farming around the world, due to treatment costs, labor, poor performance, growth retardation and deaths [ 1 ]. Despite scientific studies and chemotherapeutic advances on neonatal calf diarrhea, the disease still leads to high morbidity and mortality [ 1 , 2 ]. Diarrhea of especially with infectious origin (bacterial, viral and parasitic) occurs in the neonatal period, is commonly caused by E. coli , cryptosporidium, rotavirus and coronaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Several G genotypes (G6, G8, and G10) and P genotypes (P [1], P [5], P [7], and P [11]) have been identi ed in the Chinese cattle population. Notably, the only study conducted previously revealed that G6 and P [5] are common G and P genotypes among dairy calves in certain regions of China, with G6P being the dominant genotype combination (Liu et al, 2021). G10 is only popular in some regions.…”
Section: Introductionmentioning
confidence: 99%